2021
DOI: 10.1002/agj2.20908
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drought tolerance in different genotypes of foxtail millet during the entire growth period

Abstract: Drought significantly affects foxtail millet [Setaria italica (L.) Beauv.] yield, and its adverse effects can be mitigated via genetic improvement to generate drought‐tolerant varieties. This study aimed to screen drought‐tolerant materials and genes in foxtail millet germplasm resources to improve the efficiency of breeding for drought tolerance. A field experiment was conducted in a randomized incomplete block design (α‐lattice design) and repeated thrice with 30 foxtail millet genotypes treated under drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Recently, studies also suggested that foxtail millet is promising as anti-hyperglycemic, anti-cholesterol, and antihypertension (Sabuz et al, 2023). Several studies also reported the adaptive nature of foxtail millet to unfavorable environmental conditions and abiotic stresses, such as drought (Xiao et al, 2021) and salinity (Ardie et al, 2015;Akter et al, 2020). Regardless of the colossal importance of this species, foxtail millet still needs to strengthen its crop utilization in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies also suggested that foxtail millet is promising as anti-hyperglycemic, anti-cholesterol, and antihypertension (Sabuz et al, 2023). Several studies also reported the adaptive nature of foxtail millet to unfavorable environmental conditions and abiotic stresses, such as drought (Xiao et al, 2021) and salinity (Ardie et al, 2015;Akter et al, 2020). Regardless of the colossal importance of this species, foxtail millet still needs to strengthen its crop utilization in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Drought is the most Agriculture 2023, 13,1940 2 of 13 important abiotic factor limiting global production [2]. The sustainable development of agricultural production in this region has been restricted by natural and human factors for a long time [3]. The reasons can be divided into three factors.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional and health benefits of foxtail millet include its low glycemic index (Arora et al 2023), high protein and dietary fiber content, and anti-oxidant potential (Goudar et al 2023). Foxtail millet has also been reported to show comparable tolerance to salinity (Ardie et al 2015;Akter et al 2020) and drought (Xiao et al 2021) stresses, indicating the adaptive nature of the species to adverse environmental conditions. Nahar et al (2018) reported that salttolerant foxtail millet accession could maintain its dry matter and grain yield at the salinity level of 6 dS.m -1 , while Krishnamurthy et al (2014) evaluated 155 foxtail millet accessions under soil saturated with 100 mM NaCl and identified 13 highly tolerant foxtail millet accessions.…”
mentioning
confidence: 99%